Changes of renal transporters in the kinetic process of VCM-induced nephrotoxicity in mice. Issue 4 (9th June 2021) - Li, Hongjing; Yang, Qiaoling; Gui, Mingzhu; Ding, Lili; Yang, Li; Sun, Huajun; Li, Zhiling
Abstract: Renal transporters involved in tubular excretion pathway are considered to be the key concern in drug evaluations in nephrotoxicity. However, the relationship between the alternation of renal transporters and the kinetic process of vancomycin (VCM)-induced nephrotoxicity has not been fully elucidated. The present study investigated the alteration of renal transporters expression in the kinetic process of VCM-induced nephrotoxicity in mice. C57BL/6 mice were administrated with normal saline or VCM for 7 days. Biochemical and pathological analyses were conducted to investigate the nephrotoxicity induced by VCM administration. Renal oxidative status, plasma, and kidney content of VCM were monitored. Quantitative real-time polymerase chain reaction and immunohistochemistry analyses were performed to analyze the expression of renal transporters. Finally, our data showed that the exposure of VCM (400 mg/kg) caused a slight nephrotoxicity in mice, whereas exposure of VCM (600 mg/kg) resulted in the severe nephrotoxicity in mice as evidenced by biochemical parameters and renal morphological changes. In addition, the accumulation of VCM in kidney is higher than plasma. Interestingly, VCM (600 mg/kg, body weight) resulted in the induction of Oct2–Mate1 and Oat1/3–Mrp2/Mrp4/Bcrp pathways. However, VCM (400 mg/kg, body weight) caused the induction of Oct2–Mate1/Mate2 and Oat1/3–Mrp4/Bcrp pathways. The changes of renal transporters in association with the kinetic process of VCM-induced nephrotoxicity may exert important practical implications for its optimal use in clinic.